Animal models of brain maldevelopment induced by cycad plant genotoxins. Issue 4 (December 2013) - Kisby, Glen E.; Moore, Holly; Spencer, Peter S.
<x xml:space="preserve">Abstract</x> Cycads are long‐lived tropical and subtropical plants that contain azoxyglycosides (e.g., cycasin, macrozamin) and neurotoxic amino acids (notably β‐N‐methylamino‐l‐alanine l‐BMAA), toxins that have been implicated in the etiology of a disappearing neurodegenerative disease, amyotrophic lateral sclerosis and parkinsonism‐dementia complex that has been present in high incidence among three genetically distinct populations in the western Pacific. The neuropathology of amyotrophic lateral sclerosis/parkinsonism‐dementia complex includes features suggestive of brain maldevelopment, an experimentally proven property of cycasin attributable to the genotoxic action of its aglycone methylazoxymethanol (MAM). This property of MAM has been exploited by neurobiologists as a tool to study perturbations of brain development. Depending on the neurodevelopmental stage, MAM can induce features in laboratory animals that model certain characteristics of epilepsy, schizophrenia, or ataxia. Studies in DNA repair‐deficient mice show that MAM perturbs brain development through a DNA damage‐mediated mechanism. The brain DNA lesions produced by systemic MAM appear to modulate the expression of genes that regulate neurodevelopment and contribute to neurodegeneration. Epigenetic changes (histone lysine methylation) have also been detected in the underdeveloped brain after MAM administration. The DNA damage and epigenetic changes produced by MAM and, perhaps by chemically related substances (e.g., nitrosamines, nitrosoureas, hydrazines), might be an important mechanism by which early‐life exposure to genotoxicants can induce long‐term brain dysfunction. Birth Defects Research (Part C) 99:247–255, 2013. © 2013 Wiley Periodicals, Inc.